Endotracheal Tube Size and Post-Operative Sore Throat in Women - Ali, Mehar; Kumar, Anil; Kumar, Kelash; Farjad Sultan, Syed; Shah, Mubarak; Kumar, Sandeep (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the proportion of women with postoperative sore throat an hour after elective surgery in women intubated with a size 6 endotracheal tube versus size 7 endotracheal tube. Study design: Randomized controlled trial Place and duration of study: Department of Anesthesiology, The Indus Hospital, Karachi from 22-09-2016 to 2109-2017. Methodology: Patients were divided two equal groups through randomization i.e. endotracheal tube size 6 versus endotracheal tube size 7. Prior to intubation the endotracheal tube is to be lubricated with normal saline. In group ETT 6, trachea intubated with a high volume low pressure endotracheal tube with internal diameter 6.0 and in group ETT 7 with a 7.0 diameter tube respectively. Immediately after intubation the endotracheal tube was verified by a five-point auscultation technique and the cuff inflated with room air until no air leakage could be heard. No humidifiers or moisture exchangers were used. Results: The mean age of ETT 6 and ETT 7 group was 34.36±9.46 and37.34±10.96 years respectively. The mean duration of surgery in ETT 6 and ETT 7 group was 117.70±30.57 and 125.17±55.0 minutes respectively. When both groups were postoperative sore throat was noted in 38 (59.4%) in ETT 6 group whereas 62 (96.9%) noted in ETT7 group (p=0.0001). Conclusion: Highly significant difference was found in postoperative sore throat between the group endotracheal tube size 6 in comparison to the group endotracheal tube size 7.